C70. Performing Percutaneous Coronary Intervention in Dextrocardia: A Case Report. (23rd November 2021) - Syafar, R H; Khairat, M; Syukri, M
Abstract: Background: Dextrocardia is defined as the heart location in the right hemithorax with the apex pointing inferiorly and to the right. Performing percutaneous coronary intervention (PCI) in patient with dextrocardia can be difficult and requires some modification. Case Summary: A 55-years old male with chest pain 3 hours before admission, apex in right side, a chest X-ray confirm the heart in the right hemithorax, electrocardiogram (ECG) was consistent with dextrocardia and showed inferior ST-segment elevation myocardial infarction (STEMI). We performed primary PCI with femoral access. During coronary angiography, it was a challenge to engage the diagnostic catheter to both of ostium right and left coronary artery. Coronary angiography showed total occlusion in the proximal of right coronary artery (RCA). We inversed the engagement technique and radiological angles for RCA from the left anterior oblique 35º to the right anterior oblique 30º and finally revascularization could be done easier. Discussion: Performing PCI in patient with dextrocardia can be challenging. Inversion the engagement technique and radiological angles and views will give an advantage to the operator for imaging and doing intervention. Using image reversal technology is also help to get the image like a normal position.